Photodegradation of reactive red 120 using hybrid oxalate-pyrite/chitosan catalyst - Nur Ain Fatihah, Ismail (2024)
The textile sector plays a vital role in our economy, but it produces wastewater containing hazardous dyes, pigments, suspended and dissolved solids, and untreated heavy metals. These contaminants are often released directly into the environment, affecting soil and water receptors, and thereby posing a significant threat to the environment. Some of these dyes, such as Reactive Red 120 (RR120), are known for their toxic and potentially carcinogenic nature, impacting both human health and aquatic ecosystems. Additionally, RR120, widely used in the textile industry, poses a risk to aquatic systems due to its low biodegradability. Addressing cost and environmental concerns, the objective is to study the performance of hybrid Oxalate-pyrite/Chitosan and to study the effect of pH (3-11), catalyst dosage (0.5-6.0 g/L), and concentration of organic pollutants (5-20 mg/L) in hybrid photocatalyst/adsorbent in photodegradation of RR120 under visible light irradiation. The results show that the percentage of the performance of the hybrid catalyst was 47.31% superior compared to oxalate-pyrite was 14.71% and chitosan was 31.41%. The optimal degradation percentages of RR120 in the initial concentration condition of 5 mg/L RR120 were 47.31% at pH 7 and catalyst dosage 0.5g/L. Notably, higher degradation rates correlate with lower initial pollutant concentrations and higher catalyst dosage. The application of this hybrid catalytic system holds great potential for treating wastewater generated by various industries, including but not limited to textile materials, paper, plastic, cosmetics, and others.